Effect of a Desensitizing Varnish on Microleakage of Two Self-Etch Adhesives - Saffarpour, Anna (J Dent (Tehran), 2015)
OBJECTIVES: The aim of this in-vitro experimental study was to assess the effect of application of a desensitizing varnish on the enamel and dentin marginal seal. MATERIALS AND METHODS: Seventy-two freshly extracted, intact human premolar teeth were divided into four groups (n=18). Class V cavities (3mm in length, 2mm in width and 2mm in depth) were prepared on the buccal surface of each tooth. The following sealing materials were applied in the four groups: One-step Clearfil S3 Bond (S3) self-etch adhesive, two-step Clearfil SE Bond (SE) self-etch adhesive, S3 Bond+ VivaSens desensitizing varnish (VS+S3) and Clearfil SE Bond + VivaSens (VS+SE). The cavities on the teeth were then incrementally filled with Z350 light-cure composite. The teeth were stored in distilled water for 24 hours at 37°C, and were then thermocycled for 1000 cycles. Then, all the specimens were prepared for dye penetration test and were immersed in 2% basic fuchsin dye and incubated at 37°C for 24 hours. The teeth were then sectioned buccolingually along the center of restorations with a diamond disk. Microleakage at the tooth-restoration interface was assessed in the enamel and dentin margins blindly using dye penetration under a stereomicroscope at ×20 magnification. RESULTS: There was significantly greater leakage at the enamel and dentin margins in group VS+SE than in group SE; also, these values were higher in group VS+S3 than in S3. CONCLUSION: Combined application of desensitizing varnish and self-etch adhesives seems to increase microleakage in composite restorations. Thus, its application is not suggested.